IMPLEMENTASI METODE PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) DALAM MENINGKATKAN KOMPETENSI PENDIDIKAN AGAMA BUDI PEKERTI PADA SISWA KELAS VII SMP MANBAUL ULUM BONDOWOSO - Anis Sulalah, Asia (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2023)
One of the learning methods that involve students' participation is the co-operative learning method. In the cooperative learning method, the emphasis is more on the learning process in the group rather than doing something together with the group.. The objectives of this study were to improve: (1) overall student activeness of students in class VII of SMP Manbaul Ulum Bondowoso in the 2022/2023 academic year, (2) learning outcomes of students in class VII of SMP Manbaul Ulum Bondowoso. The methodology of this research is classroom action research. The research subjects were the seventh grade students of Manbaul Ulum Bondowoso Junior High School in the 2022/2023 academic year, a total of 40 students. Data collection techniques in this study were carried out through activities such as: (a) observation of student activeness during learning activities; (b) interviews with students; (c) daily tests. The procedure for implementing the action includes: (a) action planning; (b) action implementation; (c) observation; (d) analysis and reflection. The results of the study have increased when compared to before the application of the GI method, namely in the aspect of enthusiasm in KBM in cycle I, namely indicator BS = 5%; B = 70%; C = 22.5%; K = 2.5% and in cycle II indicator BS = 17.5%; B = 67.5%; C = 15%. The measurement of the cooperation aspect between students has increased, namely in cycle I indicator B = 22.5%; C = 70%; K = 7.5% and in cycle II indicator BS = 2.5%; B = 32.5%; C = 60%; K = 5%. Measurement of aspects of expressing opinions to solve problems has increased, namely in cycle I indicator B = 20%; C = 47.5%; K = 32.5% and in cycle II indicator BS = 7.5%; B = 22.5%; C = 57.5%; K = 12.5%. Measurement of the aspect of asking questions also increased, namely in cycle I the indicator BS = 2.5%; B = 5%; C = 67.5%; K = 15% and in cycle II the indicator BS = 7.5%; B = 22.5%; C = 57.5%; K = 12.5%. The average daily test of students in cycle II also increased by 1.05 (cycle I = 6.31; cycle II = 7.36). So it can be concluded that the Group Investigation cooperative learning method can improve student activeness and student learning outcomes.